Problems with open access publishing in radiology - Crim, Julia (2020)
OBJECTIVE. Open access publishing has grown exponentially and can be a means of increasing availability of scientific knowledge to readers who cannot afford to pay for access. This article discusses problems that can occur with open access and offers suggestions for ameliorating the problems facing radiology research because of poor-quality journals. CONCLUSION. Open access literature has loosed an avalanche of information into the radiology world, much of which has not been validated by careful peer review. To maintain academic integrity and serve our colleagues and patients, radiologists need to guard against shoddy science published in deceptive journals.
DOI: 10.2214/AJR.20.22835
Keywords: deceptive journal; open access; peer review; predatory journal